Production of Polimedia by University Professors and Degree of Acceptance in the Dominican Republic - Antonio Palacios-Rodríguez; Julio Cabero-Almenara; Ángel Puentes-Puente (Universidad Autónoma de Baja California, 2022)
The use of video in distance education contexts and in virtual training is essential. This study presents the results of an experience with 114 university professors from two universities in the Dominican Republic who carried out training activities on the pedagogical bases of the Polimedia systems. The degree of acceptance of the Polimedia system was measured through an adaptation of the Technology Acceptance Model (TAM) developed by Davis in 1989, and the significance of different sociodemographic variables in the model was analyzed. The results demonstrate the high degree of teacher acceptance of the Polimedia system and its relationship with variables such as experience with ICT, as well as the robustness of the TAM. This strengthens the need to establish training plans that focus less on technological aspects and more on the pedagogical dimension.